Integrated tacit knowledge sharing model among medical practitioners over social media with moderator and mediator interaction effect - Amidi, Asra (2018)
Codification of tacit knowledge is significant challenge of knowledge management. The importance of tacit knowledge has been pointed out in relation to decisionmaking, time-management, quality and competitiveness. Tacit knowledge of medical practitioners is an important source of experiential know-how. However, due to various operational and technical reasons, such health-care knowledge is not entirely harnessed and put into professional practice. There are still issues with the sociotechnical factors that influence the success of knowledge management implementation in the dissemination of tacit knowledge. Many of the traditional methods of knowledge diffusion like manuals and lectures are unsuitable for tacit knowledge. Hence, with the advent of social web tools, several studies argued that these new technologies may provide new opportunities to facilitate tacit knowledge sharing among medical practitioners. In spite of these arguments, there is still a lack of understanding and an empirical research on how social media may facilitate tacit knowledge sharing. The First objectives of this study are to explore the potential contributions of sociopersonal and technical factors which support tacit knowledge sharing among medical practitioners in social media. The second objective of the study was to propose an integrated tacit knowledge sharing model among medical practitioners via social media. The third objective of this study is to develop and evaluate the prototype of the tacit knowledge sharing model. Critical review of existing model and synthesizing the component of existing model was conducted to identify the factors influencing tacit knowledge sharing over social media. There are two influential dimensions namely socio personal and technical were identified. Therefore, conceptual model of this study was developed. Next, experts in knowledge management and social media review and validate the conceptual model. A pilot study was conducted to have the reliability and validity of the instrument. The empirical study was conducted to validate tacit knowledge sharing model. There are 366 medical practitioner in the state of Selangor in Malaysia participated in this study. The collected data was analysed using Structural Equation Modelling (SEMPLS). The empirical results showed that the model properly fit the data and the structural model demonstrated that the technical factors: perceived ease of use, perceived usefulness and perceived enjoyment, significantly played a positive role in tacit knowledge sharing. The analytical results also revealed that the socio-personal factors which comprise of trust, motivation, self-efficacy, performance expectation and frequency of use of social media, have positive significant effect on tacit knowledge sharing whereas commitment influence was not significant. Conclusively, attitude to use social media has a partial mediating effect on the relation between the technical factors and tacit knowledge sharing. On the other hand however, the results were supportive of the moderating effect of work experience on attitude towards using social media and the technical factors (except for perceived ease of use which was not significant). Based on the literature review and empirical study results a model named as “Integrated tacit knowledge sharing model among medical practitioners over social media” was proposed. A prototype named as Medical Knowledge Sharing (MEDKSH) was developed based on the proposed model. Then, an expert validation was conducted to verify the model. The analysis of the four expert reviewers revealed that the prototype has the potential to support tacit knowledge sharing. As for the evaluation of acceptance among the users of MEDKSH, a technology acceptance test was conducted, with 51 participants. The results from the survey indicated that MEDKSH is an effective, easy, enjoyable and useful tool that can help medical practitioners to share tacit Therefore MEDKSH can be used by medical practitioner in performing their work, and sharing their work experiences and ideas. The proposed model is unique in terms of contributing and updating the existing literature in the area of ICT support for tacit knowledge sharing, in particular, by demonstrating that social media is one of the recent enablers of tacit knowledge sharing. A major contribution of this study is the provision of new theoretical and practical insights that help explain how socio personal and -technical factors affect tacit knowledge sharing in social media. It is hoped that these insights will help builders and managers of knowledge-based virtual communities better promote online knowledge sharing behaviors and improve the sustainability of such communities in the future.